Endovascular thrombectomy in young patients with stroke. Issue 4 (April 2023) - Weller, Johannes M; Dorn, Franziska; Meissner, Julius N; Stösser, Sebastian; Beckonert, Niklas M; Nordsiek, Julia; Kindler, Christine; Deb-Chatterji, Milani; Petzold, Gabor C; Bode, Felix J
Background: Endovascular treatment (ET) is standard of care in patients with acute ischemic stroke due to large vessel occlusion, but data on ET in young patients remain limited. Aim: We aim to compare outcomes for young stroke patients undergoing ET in a matched cohort. Methods: We analyzed patients from an observational multicenter cohort with acute ischemic stroke and ET, the German Stroke Registry—Endovascular Treatment trial. Baseline characteristics, procedural parameters, and functional outcome at 90 days were compared between young (<50 years) and older (⩾50 years) patients with and without nearest-neighbor 1:1 propensity score matching. Results: Out of 6628 acute ischemic stroke patients treated with ET, 363 (5.5%) were young. Young patients differed with regard to prognostic outcome characteristics. Specifically, National Institutes of Health Stroke Scale (NIHSS) at admission was lower (median 13, interquartile range (IQR) 8–17 vs. 15, IQR 9–19, p < 0.001), and prestroke dependence was less frequent (2.9% vs. 12.2%, p < 0.001) than in older patients. Compared to a matched cohort of older patients, ET was faster (time from groin puncture to flow restoration, 35 vs. 45 min, p < 0.001) and intracranial hemorrhage was less frequent in young patients (10.0% vs. 25.9%, p < 0.001). Good functional outcome (modified Rankin Scale (mRS) 0–2) at 3 months was achieved more frequently in young patients (71.6% vs. 44.1%, p < 0.001), and overall mortality was lower (6.7% vs. 25.4%, p < 0.001). Among previously employed young patients (n = 177), 37.9% returned to work at 3-month follow-up, while 74.1% of the remaining patients were still undergoing rehabilitation. Conclusion: Young stroke patients undergoing ET have better outcomes compared to older patients, even when matched for prestroke condition, comorbidities, and stroke severity. Hence, more liberal guidelines to perform ET for younger patients may have to be established by future studies.